An Analysis Of Six Scientific- Grade Book Content According To High Order Thinking Skills - Abdullah Darwish Hussein, Asst . Prof. Dr . ilham jabbar faris (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to: Determine higher-order thinking skills (knowledge organizing, applying, analysis, generating or productivity, incorporation and Integration, Evaluation), which are included in the mathematics textbook for the sixth scientific grade The researchers used the descriptive-analytical approach to analyze the content of the mathematics book for the sixth scientific grade for the academic year 2020/2021 AD, which is approved for teaching in the schools of the Ministry of Education in Iraq, in order to determine the higher-order thinking skills (knowledge, organizing, applying, analysis, generating or productivity, and Integrating or synthesis, Evaluation) To achieve the goal of the research, the researchers analyzed the mathematics book for the sixth scientific class according to higher-order thinking skills. They found the following result: - - The content of the mathematics curriculum for the sixth grade science for the academic year 2020-2021 AD contains higher-order thinking skills (knowledge, organizing, applying , analysis, generating or productivity, incorporation and Integration, Evaluation) in different percentages The researchers concluded to a set of conclusions and recommendations and proposals.